Coping with HIV and AIDS in marginal communities: a case study of Chivanhu Settlement in Nemanwa, Masvingo, Zimbabwe - Makonese, Loveness (Rhodes University, Faculty of Humanities, Department of Sociology, 2013)
This thesis seeks to understand and analyse HIV and AIDS and rural livelihoods in Zimbabwe with particular reference to an isolated and marginalised informal settlement called Chivanhu in Masvingo Province. The focus is specifically on questions around HIV susceptibility, AIDS vulnerability and household resilience. In this regard, it is important to recognise that HIV and AIDS cannot be lumped together as one medical or social condition. Rather, there is a progression from HIV infection to AIDS-related chronic illnesses to possible death, and livelihood strategies often alter along this HIV and AIDS time-line. Zimbabwe for over a decade now has gone through a series of economic and political crises which have impacted detrimentally on both urban and rural livelihoods, even for those households which are not directly affected by the HIV and AIDS pandemic. With the economy in free-fall, households have had to pursue a range of livelihood strategies in order to sustain themselves. These socio-economic conditions have in many ways facilitated susceptibility to HIV infection and vulnerability to AIDS. Many studies have examined this in relation to wellentrenched and stable communities in rural Zimbabwe. But the livelihood dynamics for such communities are significantly different to more unstable and informal settlements like Chivanhu, as thesis seeks to show. At the same time, the thesis offers a longitudinal study which is able to map the changes to the livelihoods of infected and affected households in Chivanhu. Though recognising the debilitating effects of the pandemic on these households, it also raises questions about the possible resilience of certain households despite great adversity. In doing so, it goes beyond the individual and household levels of analysis to consider the role of clusters (or groups of households) in responding to the impacts of HIV and AIDS. In this regard, particular emphasis is placed on gender and orphanhood. In the end, the thesis offers a nuanced analysis of the everyday complexities and challenges for affected households in a marginalised and informal rural community in Zimbabwe and thereby makes a contribution to re-theorising HIV and AIDS and rural livelihoods more broadly.
Keywords: Uncatalogued